Surgical correction of labial fusion with vaginoplasty in a cat. Issue 6 (June 2013) - Plavec, Tanja; Pavlin, Darja
A spayed female domestic shorthair cat was first examined at the age of 16 months because of persistent licking of the perineal area. The cat had a grossly enlarged and oedematous vulva with pronounced superficial pyoderma of the perivulvar area, which responded favourably to systemic antibiotics, analgesics and local corticosteroids. A month after the initial examination, the cat was re-presented owing to pollakiuria, stranguria and dyschesia. The oedema of the vulva had disappeared and the vulvar labia were fused together; there was only a fistulous tract with a diameter of 1 mm present in the area of the vulva, and the cat strained to urinate through that opening. A contrast study revealed normal transit through the lower urinary tract, but labial adhesions resulted in the development of dilation cranially, where the vaginal vestibule was supposed to be. Vaginoplasty was subsequently performed, the cat recovered normally and, 10 months after the procedure, the lumen of the vaginostoma is preserved and the cat is urinating without difficulty.